2020
DOI: 10.1016/j.fawpar.2020.e00097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a modified method for the detection of Cryptosporidium oocysts on spinach leaves

Abstract: Despite the infection risk associated with the consumption of contaminated food, techniques for recovering and detecting Cryptosporidium oocysts from fruit and vegetables are generally inadequate due to the variable recovery efficiencies and high reagent costs, such as those presented by ISO 18744:2016 “Microbiology of the food chain -Detection and enumeration of Cryptosporidium and Giardia in fresh leafy green vegetables and berry fruits”. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Before 2017, only 6 cryptosporidiosis outbreaks in France were reported in the literature ( Beaudeau et al, 2008 ; Dalle et al, 2003 ; Mosnier et al, 2018 ). Many reasons could explain the increased number of reported cases of cryptosporidiosis outbreaks in France: i) the proactive monitoring of the CNR-LE-Cryptosporidiosis, ii) the growing number of laboratories in the CNR-LE-Cryptosporidiosis network, iii) the democratisation of syndromic and multiplex molecular methods allowing parasitological investigations which were not initially suspected, and iv) the improvement of food and environmental screening methods ( de Roubin et al, 2002 ; Razakandrainibe et al, 2020 ; Utaaker et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before 2017, only 6 cryptosporidiosis outbreaks in France were reported in the literature ( Beaudeau et al, 2008 ; Dalle et al, 2003 ; Mosnier et al, 2018 ). Many reasons could explain the increased number of reported cases of cryptosporidiosis outbreaks in France: i) the proactive monitoring of the CNR-LE-Cryptosporidiosis, ii) the growing number of laboratories in the CNR-LE-Cryptosporidiosis network, iii) the democratisation of syndromic and multiplex molecular methods allowing parasitological investigations which were not initially suspected, and iv) the improvement of food and environmental screening methods ( de Roubin et al, 2002 ; Razakandrainibe et al, 2020 ; Utaaker et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since 2016, an international standardardized method exists for the detection and enumeration of Cryptosporidium (and Giardia ) in fresh leafy green vegetables and berry fruits: ISO 18744:2016. However, the recovery of Cryptosporidium oocysts varies according to food matrices, sometimes demonstrating weak performances (especially with saponin-rich matrices) ( Razakandrainibe et al, 2020 ; Utaaker et al, 2015 ). Thus, Cryptosporidium screening from food matrices appears very complicated and sensitivity is low.…”
Section: Resultsmentioning
confidence: 99%
“…Several modifications to this standard method for recovering these parasites to increase recovery efficiency as well as lower costs have been published by Utaaker et al (2015) . On spinach leaves, Razakandrainibe et al (2020) also reported that the recovery of Cryptosporidium from saponin-rich leaves, such as spinach ( Spinacia oleraceae ), can be increased by using an alkaline solution instead of the acidic 1 M glycine buffer recommended in ISO 18744:2016. In the present study, an alkaline detergent elution buffer at pH 8 has been employed; however, Cryptosporidium oocysts counts on spinach leaves remained zero.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, the oocyst recovery was realized according to the ISO 18744:2016 "Microbiology of the food chain -Detection and enumeration of Cryptosporidium and Giardia in fresh leafy green vegetables and berry fruits" method with some modifications. The pH of 1 M glycine elution buffer (5.5) was adjusted to 3 for better recovery (data not shown), and for each step, samples were centrifuged at 3000× g for 30 min at 4 • C. Before oocyst purification by IMS, pellets were resuspended, and 2 mL of a detergent solution containing 1% SDS (Sigma), 0.1% Tween 80 (Sigma), and 0.001% antifoam Y (Sigma) were added as described by Razakandrainibe et al [27]. After centrifugation, pellets were resuspended in 7 mL of PBS, and oocysts were recovered by IMS (Isolate, TCS Biosciences, Buckingham, UK).…”
Section: Lamb's Lettuce: Cryptosporidium Oocysts Spiking Recovery and Cell Infectionmentioning
confidence: 99%